Effects of Dietary Guanidinoacetic Acid on the Feed Efficiency, Blood Measures, and Meat Quality of Jinjiang Bulls - Li, Zengmin; Liang, Huan; Xin, Junping; Xu, Lanjiao; Li, Meifa; Yu, Hanjing; Zhang, Wenjing; Ge, Yu; Li, Yanjiao; Qu, Mingren (Frontiers in Veterinary Science, 2021)
An experiment was conducted to determine the effects of supplementing the diet of Jinjiang bulls with guanidinoacetic acid (GAA) on their feed efficiency (feed efficiency were evaluated with feedlot average daily gain (ADG), average daily feed intake (ADFI), and feed-to-gain ratio (F:G)), blood measures, and meat quality. Forty-five Jinjiang bulls (24 ± 3 months old and 350.15 ± 30.39 kg by weight) were randomly distributed among five experimental units (each n = 9) and each unit was randomly fed with one of five diets (concentrate: roughage ratio of 60:40): (1) control; (2) 0.05% GAA; (3) 0.1% GAA; (4) 0.2% GAA; and (5) 0.4% GAA, respectively. After a 52-d feeding trial, five bulls from the control group and five bulls from the optimal GAA supplementing group were randomly selected and slaughtered for collection of the longissimus dorsi (LM) and semitendinosus (SM) muscles to determine meat quality. The results showed that dietary GAA improved the ADG, decreased the value of F:G, and affected blood measures and antioxidant variables. Supplementing 0.2% GAA into the diet was optimal for feeding efficiency and most of the measured blood measures. Supplementing 0.2% GAA into the diet increased the a*(redness) values, and b* (yellowness) values, and the amount of creatine kinase (CK), muscle glycogen, creatinine (CRE), and laminin (LN) in LM muscles. However, it decreased the drip loss, L* (lightness) value, and lactate dehydrogenase (LDH) content of LM muscles. Drip loss and shear force decreased in SM muscles, as did the amount of type IV collagen (CV–IV). In conclusion, supplementing 0.2% GAA into the diet could enhance feed efficiency to improve beef growth and meat quality.